Kajian Besaran Erosi dengan Pengaruh Panjang Alur Terhadap Estimasi Erosi dengan Metode USLE - Santoso, Arief Adkha; Rizalihadi, Maimun; Fauzi, Amir (Journal of The Civil Engineering Student, 2025)
Erosion may cause loss of topsoil (top soil) and nutrient elements which are very important for growing plants on agricultural land. So far, the estimation of soil erosion can be done using USLE method. This method is limited only for the estimation of the soil erosion in the form of sheet erosion. In fact, not all soil is in the form of complete sheets, but it also in the form of rill. This study aims to look at the effect rill density with varian slope and rainfall intensity against soil erosion with no vegetation, so that the extent of the rill effect to erosion can be pictured. Erosion measurements performed on the variation of slope 00, 30dan 60, variation rain pressure (10, 30 and 50) Kpa and variation of density plot (0, 1, 2 and 3) m / m2. The results indicate that soil erosion is increasing about 1.05-2.13 times higher than erotion on a field without rill.